2001
DOI: 10.1002/lsm.1138
|View full text |Cite
|
Sign up to set email alerts
|

Laser‐induced shock waves enhance sterilization of infected vascular prosthetic grafts

Abstract: This study demonstrates that laser-generated shock waves have no effects alone, but can enhance the effectiveness of antibiotics against bacteria associated with prosthetic vascular graft biofilms, suggesting that this treatment may be of value as adjunctive therapy for prosthetic graft infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Unlike standard laser technologies, there is no direct contact of thermal energy from the laser system to the tissue being treated. Early work by Krespi et al and Nigri et al strongly suggested the efficacy of LGS in disrupting biofilms in vitro , while Doukas et al expanded on this research by showing that LGS increased transdermal drug delivery by affecting surface permeability . Our group has further expanded on LGS applications in infected wounds in in vitro models , and is currently underway in translating this concept to in vivo studies.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Unlike standard laser technologies, there is no direct contact of thermal energy from the laser system to the tissue being treated. Early work by Krespi et al and Nigri et al strongly suggested the efficacy of LGS in disrupting biofilms in vitro , while Doukas et al expanded on this research by showing that LGS increased transdermal drug delivery by affecting surface permeability . Our group has further expanded on LGS applications in infected wounds in in vitro models , and is currently underway in translating this concept to in vivo studies.…”
Section: Discussionmentioning
confidence: 93%
“…Previously, it has been shown that LGS therapy can remove bacterial biofilm grown in a polystyrene dish, and the treatment resulted in an immediate 55% reduction in colony‐forming unit (CFU) count of bacterial cultures grown on agar . Furthermore, work by Nigri et al demonstrated that LGS therapy in combination with vancomycin therapy can reduce S. epidermidis CFU count on vascular prosthetic grafts . Another study by Krespi et al showed that LGS therapy alone can be effective in removing Pseudomonas aeruginosa biofilms in vitro from commonly used prosthetic materials used in otolaryngology, such as sutures, screws, and tympanostomy tubes .…”
Section: Introductionmentioning
confidence: 99%
“…Biofilms remaining after exposure to shockwaves are more susceptible to antibiotics than biofilms not exposed to shockwaves [ 105 ]. Another method used a black polystyrene cover, which was placed over a prosthetic graft with an antibiotic solution between the cover and the graft [ 106 ]. When the laser light hits the polystyrene cover, the light energy is absorbed by the material, causing an thermal expansion resulting in a shockwave which disrupts the biofilm [ 106 ].…”
Section: Biofilm Dispersion: the Two Mechanismsmentioning
confidence: 99%
“…Krespi et al demonstrated, through confocal miscroscopy, the ability of 10–20 low-energy laserinduced pressure waves to disperse bacterial cells within biofilm off of small suture, stent, and bone screw [15], [16]. Nigri et al demonstrated no effect of laser-induced shock waves (SW) alone to biofilms, but clearly observed SW permeabilizing effects on biofilms, reporting a 102 improvement of antibiotic effectiveness when coupled with SW treatment of eight pulses at 60 MPa of pressure [17]. …”
Section: Introductionmentioning
confidence: 99%
“…However, analysis on that mechanism is currently under review. Further, it has been shown that these pressure waves have the ability to increase delivery of macromolecules through cutaneous tissue without damaging the stratum corneum [21], which can provide a secondary mechanism to treat biofilm by coupling LGS therapy with a topical antibiotic treatment, similar to [17]. …”
Section: Introductionmentioning
confidence: 99%